2006
DOI: 10.1523/jneurosci.0715-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Neural Progenitors Switch toward an Oligodendroglial Fate in Response to Increased Sonic Hedgehog (Shh) Activity: Involvement of Sulfatase 1 in Modulating Shh Signaling in the Ventral Spinal Cord

Abstract: In the embryonic chick ventral spinal cord, the initial emergence of oligodendrocytes is a relatively late event that depends on prolonged Sonic hedgehog (Shh) signaling. In this report, we show that specification of oligodendrocyte precursors (OLPs) from ventral Nkx2.2-expressing neural progenitors occurs precisely when these progenitors stop generating neurons, indicating that the mechanism of the neuronal/oligodendroglial switch is a common feature of ventral OLP specification. We further show that an exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
149
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(158 citation statements)
references
References 77 publications
8
149
1
Order By: Relevance
“…One of the key molecules involved in ventral neural tube patterning is Shh expressed both in the notochord and floorplate in vertebrates (Odenthal et al, 1996). In vitro studies have shown quail sulf1 regulates the range of Shh signalling in oligodendrial specification (Danesin et al, 2006). Given their co-expression, it is likely that sulfs may have a similar role in shaping the Shh gradient in neural tube and notochord and, therefore, modulating shh-mediated processes.…”
Section: Expression Profile Of Hs Enzymes In Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key molecules involved in ventral neural tube patterning is Shh expressed both in the notochord and floorplate in vertebrates (Odenthal et al, 1996). In vitro studies have shown quail sulf1 regulates the range of Shh signalling in oligodendrial specification (Danesin et al, 2006). Given their co-expression, it is likely that sulfs may have a similar role in shaping the Shh gradient in neural tube and notochord and, therefore, modulating shh-mediated processes.…”
Section: Expression Profile Of Hs Enzymes In Zebrafishmentioning
confidence: 99%
“…Dynamic changes in HS sulfation by the Sulfs have been shown to modulate a number of signalling molecules including Shh, Wnt, Bone Morphogenic Protein-4 (BMP4), Glial Derived Neurotrophic Factor (GDNF), Fibroblast Growth Factor (FGF), and Vascular Endothelial Growth Factor (VEGF). Sulfs control Wnt-dependent myogenesis by allowing Wnt to freely associate with its receptor (Dhoot et al, 2001), regulate oligodendroglial specification by enhancing the diffusion gradient of Shh (Danesin et al, 2006), mediate mesoderm induction and angiogenesis through an FGF/HS/ FGF receptor (FGFR) complex (Ai et al, 2003), regulate GDNF-mediated muscle innervation and regeneration (Ai et al, 2007), and also regulate BMP4 signalling by inhibiting the interaction with its cognate receptor (Freeman et al, 2008). Thus, Sulf enzymes can regulate HS-dependent signalling in both a positive and negative manner, depending on the interaction of 6-O sulfation with the HS-binding protein.…”
Section: Introductionmentioning
confidence: 99%
“…Genes encoding for Sulf enzymes have been identified in birds, mouse, rat, and human, and more recently in amphibian (Dhoot et al, 2001;Morimoto-Tomita et al, 2002;Ohto et al, 2002;Braquart-Varnier et al, 2004;Nagamine et al, 2005;Ai et al 2007;Freeman et al, 2008). During development, these enzymes are involved in regulating major signaling pathways, including Wnt, FGF, HGF, GDNF, BMP, and Shh (Dhoot et al, 2001;Ai et al, 2003;Wang et al, 2004;Viviano et al, 2004;Danesin et al, 2006, Ai et al, 2007, Freeman et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…During development, Sulf proteins are expressed in neural and mesodermal tissues (Dhoot et al, 2001, Wang et al, 2004Braquart-Varnier et al, 2004;Danesin et al, 2006;Ai et al, 2007). In the embryonic central nervous system (CNS), Sulf1 has been shown to be expressed in floor plate cells and in a subset of neural progenitors of the spinal cord, as well as in the choroid plexus (Dhoot et al, 2001;Ohto et al, 2002;Braquart-Varnier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation